2001
DOI: 10.1111/j.1572-0241.2001.03924.x
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged multi-point recording of colonic manometry in the unprepared human colon: providing insight into potentially relevant pressure wave parameters

Abstract: Prolonged, multipoint, perfusion manometry of the unprepared colon provides improved spatial resolution of colonic motor patterns and confirms the diurnal and regional variations in propagating pressure waves detected in the prepared colon. The study demonstrates differences between high amplitude propagating sequences and propagating sequence parameters that may have functional significance; and also, that the rectal motor complex is a ubiquitous pan colonic motor pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
126
1
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 112 publications
(136 citation statements)
references
References 26 publications
8
126
1
1
Order By: Relevance
“…In one study in volunteers, it was shown that out of 27 instances of perceived urge to defecate, 26 were associated with a propagated sequence, of which 62% were associated with HAPSs [121]. This study also showed that propagated sequences were more likely to result in urge during the 1 h pre-expulsive phase (as compared to the basal phase), and that sequences that propagated further were more likely to result in an urge.…”
Section: Role Of the Colonmentioning
confidence: 89%
See 4 more Smart Citations
“…In one study in volunteers, it was shown that out of 27 instances of perceived urge to defecate, 26 were associated with a propagated sequence, of which 62% were associated with HAPSs [121]. This study also showed that propagated sequences were more likely to result in urge during the 1 h pre-expulsive phase (as compared to the basal phase), and that sequences that propagated further were more likely to result in an urge.…”
Section: Role Of the Colonmentioning
confidence: 89%
“…Colonic motor activity shows a circadian pattern, in that it increases after awakening [117] and is higher during the day compared to the night [117][118][119][120]. Colonic activity also increases after meals (see above) [117,120,121]. Patients with constipation may lack the nocturnal suppression of colonic activity [122] and exhibit reduced colonic responses to food [122][123][124][125], as well as lacking spatio-temporal organization of colonic contractile patterns [126].…”
Section: Colonic Motor Activitymentioning
confidence: 93%
See 3 more Smart Citations